DEVELOPMENT OF DIGITAL ASSESSMENT TOOLS USING WORDWALL AND PLICKERS FOR CHEMISTRY LEARNING IN SENIOR HIGH SCHOOL - Sari, Ratih Permana; Hasby, Hasby; Hiskia, Evolando; Setiawaty, Sri (Lantanida Journal, 2025)
This study addresses the need for interactive digital assessment tools in chemistry learning, where traditional evaluation often fails to engage students or provide immediate feedback. Wordwall and Plickers were selected as platforms because both are widely accessible and classroom-friendly, yet their effectiveness in formative evaluation has not been systematically compared. The purpose of this research was to develop and evaluate interactive assessments based on these two applications for high school chemistry. A Research and Development (R&D) approach was applied by combining the Borg & Gall and 4-D models. The process included four stages: (1) Define analyzing curriculum requirements and learner needs; (2) Design and construct interactive items and adapt them to Wordwall and Plickers; (3) Develop expert validation covering content accuracy, construct clarity, and usability, followed by revisions and limited trials; and (4) Disseminate large-scale implementation with 200 tenth-grade students from public high schools in Aceh Province. Instruments consisted of expert validation sheets, student response questionnaires (attractiveness, ease of use, and learning benefit), and pretest–posttest assessments. The results showed high validity (CVR = 0.90), positive student responses, and significant learning gains for both platforms (N-gain = 0.70 for Wordwall, 0.64 for Plickers). No significant difference was found between them (p = 0.252), indicating that both tools are valid, practical, and effective for formative assessment in chemistry learning.